Adaptation of the Bergen Facebook Addiction Scale for a sample of Portuguese population - Leite, Ângela (2022)
The aim of this study is to adapt a Portuguese version of the original 18 items of the Bergen Facebook Addiction Scale (BFAS), via a translation / back translation process, using Confirmatory Factor Analysis (CFA) in a Portuguese sample. The sample comprised 232 respondents from the general population. The modified BFAS acquires a different factor structure from the original, keeping 4 of the main theoretical elements (subscales) and 10 of the 18 original items. The results indicate that the Portuguese version of the original BFAS presents good psychometric qualities. The statistical techniques used in the study allowed assessing the reliability and validity of the modified BFAS. Nevertheless, further uses of this scale with other samples from the Portuguese population are necessary to confirm the obtained results.